Alleviating mental health disorders through doses of green spaces: an updated review in times of the COVID-19 pandemic. Issue 1 (2nd January 2023) - Lanza-León, Paloma; Pascual-Sáez, Marta; Cantarero-Prieto, David
ABSTRACT: The COVID-19 pandemic has highlighted issues due to mental health disorders, in particular the serious consequences derived from lockdown measures. This paper aims to analyse the literature on the potential direct impact of the natural environment on mental health disorders. We have systematically reviewed the studies analysing green spaces and mental health included in this review using PubMed, Web of Science, Scopus and Cochrane Library. A retrospective time-frame is considered, covering the COVID-19 pandemic. We have found that exposure to, use and proximity to green spaces have a beneficial impact on mental health among elderly, students and patients with underlying pathologies. However, it has negative effects on the mental health of women and young adults. Exposure to and interaction with the natural environment can improve certain mental health disorders and should be taken into account for strategies and policies related to future threats to public health.